Prognostic role of left atrial enlargement in patients with implantable cardioverter defibrillators for primary prevention. Issue 1 (2nd January 2022) - Bissolino, Arianna; Andreis, Alessandro; Magnano, Massimo; Budano, Carlo; Saglietto, Andrea; Angelini, Filippo; Roagna, Edoardo; Mattivi, Simone; Peyracchia, Mattia; Errigo, Daniele; Golzio, Pier Giorgio; Castagno, Davide; et al.
Abstract: Purpose: Left atrial volume index (LAVI) is a predictor of heart failure and adverse events, irrespective of left ventricular systolic function. The role of LAVI in the prediction of appropriate implantable cardioverter-defibrillator (ICD) therapies is currently unclear and was the focus of this study. Methods: Consecutive heart failure patients with ischaemic (ICM) or idiopathic (DCM) aetiology receiving ICD for primary prevention were included. The primary endpoint was the occurrence of appropriate ICD therapies (ATs): shocks or antitachycardia pacing (ATP). Inappropriate ICD shocks were also assessed as secondary endpoint. Results: Among 198 included patients, severe left atrial dilatation (SLAE = LAVI ≥ 60 ml/m 2 ) was present in 54 (27%). SLAE patients had a higher prevalence of NYHA class ≥ III, severe mitral regurgitation and atrial fibrillation history. During a median follow-up of 45 months (IQR 25–68), ATs occurred more frequently in SLAE group (33% vs. 15%, p  = .007) as well as appropriate shocks (24% vs. 10%, p  = .014). At multivariate analysis SLAE was an independent predictor of ATs (OR 3.19, 95% CI 1.38–7.38, p  = .007). Inappropriate shocks were associated with AF during implantation ( p  = .03), but not with SLAE ( p  = .009). Conclusion: In DCM or ICM patients candidate to receive an ICD for primary prevention, a severely enlarged left atrium is a predictive factor for ATs (shocks or ATP). The risk of inappropriate shocks was increased in patients with atrial fibrillation, rather than SLAE.